CARBONATES ARE THE PERSPECTIVE MATERIALS FOR PRODUCTION OF FINING ADDITIVES FOR SILUMINS - N. V. Chajkina; V. A. Chajkin; S. P. Zadrutskij; B. M. Nemenenok; V. A. Rozum (Литьë и металлургия)
The results of investigation of creation of fining blend with modifying effect on the basis of carbonate are given.